2011
DOI: 10.1103/physreve.84.011926
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical effects on multilayered cells in nonuniform rotating fields

Abstract: We use the Maxwell stress tensor to calculate the dielectrophoretic force and electrorotational torque acting on a realistic four-shelled model of the yeast Saccharomyces cerevisiae in a nonuniform rotating electric field generated by four coplanar square electrodes. The comparison of these results with numerical calculations of the dipolar and quadrupolar contributions obtained from an integral equation for the polarization charge density shows the effect of the quadrupole contribution in the proximity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The authors have already performed a detailed study on the polarizability and electromechanical effects on multilayered cells in nonuniform rotating fields [35] where we showed that the effective polarizability of a particle consisting of N layers and immersed in a suspending medium of complex permittivityε ext = ε ext − iσ ext /ω can be determined by the equatioñ…”
Section: Polarizability and Rotational Velocity Of The Yeast Cellmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors have already performed a detailed study on the polarizability and electromechanical effects on multilayered cells in nonuniform rotating fields [35] where we showed that the effective polarizability of a particle consisting of N layers and immersed in a suspending medium of complex permittivityε ext = ε ext − iσ ext /ω can be determined by the equatioñ…”
Section: Polarizability and Rotational Velocity Of The Yeast Cellmentioning
confidence: 99%
“…For a detailed analysis of the influence of all the higher order multipolar terms induced in the cell by the nonuniform fields we refer the reader to Ref. [35]. The electrorotational torque is proportional to the out-of-phase part of the induced dipole moment and to the timeaveraged applied electric field [37,38].…”
Section: Polarizability and Rotational Velocity Of The Yeast Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…DEP methods utilize electric fields for cell rotation, which may cause irreversible damage to the target cell. 26 Finally, acoustic and microfluid methods have difficulty stabilizing 6 and accessing 19 the target cell after cell orientation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, the magnetic fields' alignment restricted the achievable cell orientations. Dielectophoresis (DEP) was introduced to rotate cells using a non-uniform electric field [59,60,61].…”
Section: Cell Orientationmentioning
confidence: 99%